Evaluating adsorption isotherm models for determining the partitioning of ammonium between soil and soil pore water in environmental soil samples - M. G. Davis; K. Yan; J. G. Murphy (Biogeosciences)
Ammonium in soil pore water is thought to participate in bidirectional exchange with the atmosphere; however, common soil nutrient analysis methods determine the bulk quantity of ammonium associated with the soil particles rather than determining the aqueous ammonium concentration. Previous works have applied the Langmuir and Freundlich isotherm equations to ammonium-enriched soils to estimate partitioning, but this may not be representative of conditions in natural, unmanaged soils. In this work, environmental soil samples were collected from green spaces in Toronto and used to evaluate several commonly used adsorption isotherm equations, including the Langmuir, Freundlich, Temkin and Toth equations, to determine their applicability in lightly managed and non-fertilized soils. We then compare ammonia emission potentials (a quantity predicting the propensity of ammonia to volatilize from a liquid reservoir) determined using a conventional high-salt extraction procedure to determine the soil ammonium content to that modelled using the Temkin and Langmuir equations and demonstrate that conventional approaches may overestimate emission potentials from soils by a factor of 5–20.